Gestational Weight Gain of Pregnant African American Adolescents Affects Body Mass Index 18 Years Later - Groth, Susan (2013)
OBJECTIVE: To determine if gestational weight gain (GWG) in adolescents is associated with long-term weight increases 12 years and 18 years after delivery of a first child and the differential effects of weight gain during pregnancy that is inadequate, the appropriate amount, and excessive based on the 2009 Institute of Medicine (IOM) recommendations. DESIGN: Secondary data analysis of data from a randomized controlled trial. SETTING: Memphis, Tennessee. PARTICIPANTS: Two hundred ninety eight (298) primiparous low-income Black women who were adolescents at the time of their first pregnancies. METHODS: Linear regression was used to examine the relationship between body mass index (BMI) at 12and 18 years postdelivery and GWG, parity, prepregnancy BMI, and smoking. RESULTS: The total sample experienced a significant BMI increase from prepregnancy to 12 years and 18 years postdelivery. More than 50% of the women had a BMI increase greater than 10 kg/m(2). By 18 years postdelivery, 85% were overweight or obese. Prepregnancy BMI and GWG had a positive significant effect on BMI 12 and 18 years later, whereas smoking had a negative effect. Those who gained excessive weight based on the IOM recommendations had a significantly higher BMI compared with those who gained appropriately. CONCLUSION: Gestational weight gain had long-term effects on BMI in a minority adolescent population. Excessive pregnancy weight gain is likely to contribute to long-term weight retention, especially if adolescents are overweight or obese when they become pregnant with their first children. Intervention during pregnancy to limit GWG has the potential of limiting long-term negative health consequences that result from overweight and obesity in minority women.